Investment Decision Factors - Sugiarto, Sugiarto; Surahman, Dedy; Sya’ban, Ma’ruf (SUSTAINABLE, 2023)
The purpose of this study was to determine the effect of financial literacy and personal income on investment decisions. Data collection was carried out by survey using a questionnaire given to 75 respondents. The results of this study indicate that Financial Literacy partially has no significant effect on Financial Behaviour, Financial Literacy partially has a significant effect on Investing Decisions, Personal Income partially has no significant effect on Financial Behaviour, Personal Income partially has a significant effect on Investing Decisions, Financial Behaviour partially has no significant effect on Investing Decisions.